The prevalence and risk factors of overweight and obesity in preschool children in the Subcarpatian region – a pilot study - Weres, Aneta; Baran, Joanna; Łuszczki, Edyta; Dereń, Katarzyna; Mazur, Artur (European Journal of Clinical and Experimental Medicine, 2016)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. A severe epidemic of lifestyle diseases, including obesity, is now one of the biggest problems of modern medicine. This is a medical problem, social and economic. The purpose of this study was to determine the impact of selected perinatal and environmental factors on the prevalence of overweight and obesity in preschool children located in the Subcarpathian region. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Material and methods. The survey was conducted in 2012, it included 200 children between the ages of 3 to 6 years (87 boys and 113 girls) from kindergartens. In children, weight loss was measured on an electronic balance and their height was also measured on medical scale. Obesity was determined on the basis of criteria developed by the International Obesity Task Force (IOTF). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Results. The prevalence of overweight and obesity among preschool children was found in 3-year-olds (6.4%), 4-year olds (11.3%), 5-year-olds (17.7%), and 6-year-olds (20.7%). <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. Body weight and mother’s BMI are factors that significantly increase the risk of obesity among children aged 3–6. Additionally, in boys, a risk factor is also the birth body length.